Italian Registry of Patients with Alpha-1 Antitrypsin Deficiency: General Data and Quality of Life Evaluation. (14th May 2015) - Luisetti, Maurizio; Ferrarotti, Ilaria; Corda, Luciano; Ottaviani, Stefania; Gatta, Nuccia; Tinelli, Carmine; Bruletti, Gisella; Bertella, Enrica; Balestroni, Gianluigi; Confalonieri, Marco; Seebacher, Christine; Iannacci, Leonardo; et al.
Abstract: Alpha1-antitrypsin Deficiency (AATD) is a rare hereditary disorder with an estimated prevalence of about 1/5000 individuals in Italy. Deficient patients are at a higher risk of developing lung emphysema and chronic liver disease. The low estimated prevalence of AATD prompted the establishment of a registry with the aim of learning more about the natural history and the quality of care of these patients. The Italian registry for AATD was established in 1996. In this study, genetic and clinical findings of Italian AATD patients are presented. Moreover, we also evaluated the changes in health-related quality of life (HRQoL) in patients with COPD and AAT deficiency over a three-year period, in relation to augmentation therapy. In a period spanning 18 years (1996–2014) a total of 422 adult subjects with severe AATD were enrolled, namely 258 PI*ZZ, 74 PI*SZ, 4 PI*SS and 86 patients with at least one rare deficient allele. The 21.3% frequency for AATD patients with at least one deficient rare variant is the highest so far recorded in national registries of AATD. The registry data allow a detailed characterization of the natural course of the disease and the level of patient care, as well as confirm the usefulness of early AATD detection.